GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 2278 species occurrences available in GBIF matching the query: Country: Spain TaxonKey: Moehringia intricata subsp. tejedensis (Willk.) J.M. Montserrat or Moehringia fontqueri Pau or Minuartia webbii McNeill & Bramwell or Dianthus inoxianus M.J. Gallego or Spergularia bourgeaei Lebel or Spergula viscosa Lag. or Erodium rupicola Boiss. or Erodium recoderi R. Auriault & G.-G. Guittonneau or Erodium paularense F. Fernández-González & J. Izco or Erodium meynieri Maire or Erodium maritimum or Erodium cazorlanum Heywood or Erodium astragaloides Boiss. & Reuter or Erodium aguilellae S. López Udias, C. Fabregat & G. Mateo or Ruta microcarpa Svent. or Gentiana lutea var. aurantiaca (M.Laínz) M.Laínz or Gentianella hispanica López Udias, Fabregat & Renob. or Galium teres Merino or Alchemilla nieto-felineri S.E.Fröhner or Sambucus palmensis Link or Rhamnus legionensis Rothm. or Salvia broussonetii Benth. or Phlomis margaritae Aparicio & Silvestre or Rosmarinus tomentosus Hub.-Mor. & Maire or Sideritis sventenii (G.Kunkel) Mend.-Heuer or Sideritis serrata Cav. ex Lag. or Sideritis reverchoni Willk. or Sideritis pumila (Christ) Mendoza-Heuer or Sideritis nervosa (Christ) Linding. or Sideritis marmorea Bolle or Sideritis lurida subsp. borgiae (J.Andrés) Luceño, Gardia Muñoz & A.González or Sideritis lasiantha Juss. ex Pers. or Sideritis javalambrensis Pau or Sideritis infernalis Bolle or Sideritis hyssopifolia subsp. caureliana Obón & D.Rivera or Sideritis guayedrae Marrero Rodr. or Sideritis glauca Cav. or Sideritis cystosiphon Svent. or Sideritis calduchii Cirujano et al. or Sideritis bolleana Bornm.. The dataset includes 2278 records from 67 constituent datasets: 1 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 2 records from Phanerogamic Botanical Collections (S). 30 records from Naturalis Biodiversity Center (NL) - Botany. 36 records from SANT Herbarium vascular plants collection. 103 records from Inventario Español de Especies Terrestres (MAGRAMA). 2 records from Banc de Germoplasma Vegetal de les Illes Balears-JBS. 6 records from MBM - Herbário do Museu Botânico Municipal. 4 records from Australia's Virtual Herbarium. 783 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 14 records from Banco de Germoplasma del Jardín Botánico Atlántico. 48 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 39 records from Herbario de la Universidad de Granada: GDA. 2 records from naturgucker. 187 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 3 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from Tropicos Specimen Data. 1 records from Naturhistorisches Museum Mainz, Botanical Collection. 9 records from Natural History Museum (London) Collection Specimens. 1 records from Inventario de Flora y Vegetación del Municipio de Enguídanos (Cuenca), 2010. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 3 records from Universität Salzburg. 108 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 39 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 131 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 18 records from Herbario de la Universidad de Almeria. 9 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 35 records from Jardín Botánico de Córdoba: Herbarium COA. 2 records from Aranzadi Zientzi Elkartea. 24 records from CIBIO, Alicante:ABH-GBIF. 3 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 11 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 62 records from Herbario de la Universidad de Sevilla. 6 records from Herbario de la Universidad de Sevilla, SEV-Historico. 24 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 2 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 19 records from Institut Botanic de Barcelona, BC. 2 records from DAO Herbarium Type Specimens. 1 records from Herbarium Berolinense. 30 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 4 records from Institut Botanic de Barcelona, BC-Histórico. 22 records from EURISCO, The European Genetic Resources Search Catalogue. 2 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 106 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 5 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 20 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 2 records from Jardín Botánico Atlántico, Gijón: JBAG. 46 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 2 records from Herbarium Senckenbergianum (FR). 8 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 22 records from Herbario de Universidad de Murcia: MUB. 19 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 2 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Carnet en Ligne. 4 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 1 records from Royal Botanic Garden Edinburgh Herbarium (E). 3 records from Botany (UPS). 1 records from Museu de Ciències Naturals de Barcelona: BGJBB. 1 records from Type herbarium, Göttingen (GOET). 6 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 1 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 14 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 154 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 2 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 5 records from Vascular Plant Herbarium, Oslo (O). 1 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 5 records from Herbarium Erlangense. 17 records from Geneva Herbarium – General Collection (G). 1 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentación y Medio Ambiente (España/Spain). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences